Search for Top Squark and Higgsino Production Using Diphoton Higgs Boson Decays - Chatrchyan, S.; Khachatryan, V.; Sirunyan, A. M.; Tumasyan, A.; Adam, W.; Bergauer, T.; Dragicevic, M.; Ero, J.; Fabjan; Friedl, M.; Fruehwirth, R.; Ghete, V. M.; et al. (American Physical Society (APS), 2014)
Results are presented of a search for a "natural" supersymmetry scenario with gauge mediated symmetry breaking. It is assumed that only the supersymmetric partners of the top quark (the top squark) and the Higgs boson (higgsino) are accessible. Events are examined in which there are two photons forming a Higgs boson candidate, and at least two b-quark jets. In 19.7 inverse femtobarns of proton-proton collision data at sqrt(s) = 8 TeV, recorded in the CMS experiment, no evidence of a signal is found and lower limits at the 95% confidence level are set, excluding the top squark mass below 360 to 410 GeV, depending on the higgsino mass.

Replaced with published version. Added journal reference and DOI
Keywords: Particle physics, LHC, CMS, Supersimmetry, Higgs boson; Top Squark; Particle physics; Large hadron collider; CMS; High Energy Physics - Experiment; High Energy Physics - Experiment (hep-ex); supersymmetry: signature; stop: mass: lower limit; info:eu-repo/classification/ddc/530; Supersymmetry; supersymmetry: symmetry breaking; Higgsino: pair production; GeV-cms; [Anahtar Kelime Yok]; CMS; Physics; ddc:530; Supersymmetry; Colliders; CERN LHC Coll; stop: cascade decay; LHC; CMS; HEP; Medicine (all); Physics and Astronomy (all); Particle physics; Higgsino: mass; final state: two-photon; jet: bottom; physics; stop: pair production; Higgsino production; p p: scattering; cms; FOS: Physical sciences; jet: multiplicity; Top squark; Physics and Astronomy (all); Colliders; CMS; Top Squark; Higgsino; mediation: gauge; info:eu-repo/classification/ddc/550; Large hadron collider; Higgs particle: radiative decay; Colliders; QC Physics / fizika; Higgsino; Supersymmetry; experimental results